Design, analysis and fabrication of bottle neck elactrode - Ngau, Kien Keong (2007)
Bottle mould making technology has become one of the most important industries nowadays. However, the bottle necks mould making process is given less attention and special tooling is needed in order to shape the mould. Bottle neck tool making process involves features consideration of its complex geometry. This project is aim to design and manufacture the bottle neck tool. This tool will be use to form a shape the workpiece to become bottle neck mould. For that, the tool design was done using Solidworks and Cimatron. The FEA method was used in electrostatic current and voltage analysis on the tool. Finally, the DFM Concurrent Costing was applied to estimate the machining cost before it proceeds into the machining stages. The results show that after FEA analysis, the values of the electrical current magnitude were stated as 1 936.07A/m2 (highest) and 11.1 649A/m2 (lowest) respectively. Meanwhile, the estimated machining cost generated from DFM software was RM 867.19. A prototype of the neck finish electrode was fabricated at the end of this project. As a conclusion, the electrode design, analysis and fabrication have achieved by using tools such as Solidworks, Cimairon, ALGOR, DFM Concurrent Costing and MasterCAM.